Pemanfaatan Teknologi IoT dalam Meningkatkan Produktivitas Tambak Udang: Studi Kasus di Desa Sidobinangun - Eka Iskandar; Trihastuti Agustinah; Achmad Jazidie; Ari Santoso; Ali Fatoni; Joko Susila; Imam Arifin; Yurid Eka Nugraha (Sewagati, 2026)
Sidobinangun Village in Lamongan Regency is a shrimp farming center experiencing declining productivity due to the degradation of pond water quality. Organic waste pollution from river flows causes pH fluctuations and high temperatures, triggering stress in shrimp and reducing yields. Furthermore, most farmers still rely on manual monitoring without adequate technological support. Through a community service program, the team designed and implemented a multistage water filtration system and an Internet of Things (IoT)-based water quality monitoring system powered by solar panels. The filtration system is composed of a combination of gravel, silica sand, palm fiber, activated charcoal, and zeolite to improve water clarity and reduce chemical contaminants. Meanwhile, the IoT system is equipped with pH, ​​temperature, TDS, DO, EC, ORP, and salinity sensors with real-time monitoring via an online dashboard. Field tests showed that both systems can operate stably and effectively, improving pond water quality and supporting farmer operational efficiency. The program also provided training to the community to ensure the sustainability of the technology. This implementation is expected to increase pond productivity and encourage the transformation of shrimp farming towards a more modern, adaptive, and sustainable system.